Flea-Borne Typhus Causing Hemophagocytic Lymphohistiocytosis: An Autopsy Case - Divya Chandramohan; Moyosore Awobajo; Olivia Fisher; Christopher L. Dayton; Gregory M. Anstead (MDPI AG, 2023)
Infection with members of the order Rickettsiales (the genera Rickettsia, Anaplasma, Orientia, and Ehrlichia) is known to cause hemophagocytic lymphohistiocytosis (HLH). The literature is scant on flea-borne typhus (FBT) being implicated in this process. We present a case of autopsy-proven HLH caused by FBT in a 71-year-old diabetic female who was initially suspected of having diabetic ketoacidosis who rapidly suffered decompensated multi-organ failure. Although she was suspected of having FBT and HLH pre-mortem, due to her rapid progression to multi-organ failure, she was transitioned to comfort care by her family five days after admission. A literature search yielded five other cases of HLH secondary to FBT, which are analyzed in this review. The literature on HLH occurring with infection due to other members of the order Rickettsiales is also surveyed.